How Do Recruiters Assess Applicants Who Express a Political Engagement? - Eline Moens; Dyllis De Pessemier; Stijn Baert (Institute of Labor Economics (IZA), 2024)
Although unequal treatment of workers based on political affiliation is prohibited in many countries, it is conspicuously understudied in the discrimination literature. In this study, we set up a vignette experiment with genuine recruiters to provide more insight into the effect of political engagement in job applicants on the assessment of their resumes by these professionals. We find that, overall, recruiters view an applicant as less creative, open-minded, empathetic and emotionally sensitive when a political engagement is expressed. These stigma are greater for candidates with a right-wing nationalist commitment. Relatedly, these candidates are assessed worse in terms of overall hireability and perceived inclination or taste among employers, colleagues and customers to collaborate with them. They are, however, seen as somewhat more assertive. In contrast to research conducted in one- or two-party systems, we do not find interactions with the political preference of the recruiter herself/himself. Overall, the effect of mentioning a political engagement in a resume is more negative when the required education level of the vacancy is high.
Keywords: D72; J21; J71; P16; C91; 330; hiring discrimination; political preference; vignette experiment